Community monitoring and security using an intelligent camera in EAT smart grids - Thananunsophon, Ketsupich; Mangalabruks, Benja; Fujii, Yusaku; Yupapin, Preecha P. (My University, 2011)
The paper purposes the use of new energy management method for monitoring sub-electrical power station security, service and maintenance. A system consists of a close circuit television (CCTV) for surveillance system, in which the electrical system prevention and monitoring can also be operated by using the thermal viewer (sensor). The consumers confident for the electricity quality will be increased by EAT smart Grid. This equipment can be installed in the system of substation in order to create stability for Thailand electricity system throughout the Smart Grids.
Keywords: Energy management; Innovative communication; Intelligent camera, Smart Grids; Thermal sensor